Effects of anomalous charged current dipole moments of the tau on the decay τ- → vτπ-π0 - Dova, María Teresa (1999)
We analyse the process τ- → vτπ-π0 allowing for anomalous weak charged current magnetic and electric dipole moment interactions and determine the effects on the differential and total decay rates. Using recent experimental data we determine the following values for the anomalous magnetic and electric dipole moment parameters, respectively: κ = 0.16±0:08; and |ǩ| = 0.88+0.25−0.35.